Envelhecimento humano e consumo : a estética, dilemas e diversidade de comportamentos - Teixeira, Micheline Machado (2015)
For women, the aging phenomenon can be more traumatic than for men. They are faced with loss of the aesthetic joviality, appearance of wrinkles, expression lines, white hair, and other physical changes, which conduce the increase consumption of cosmetics products by this audience that seeks to elevate their self-esteem and feel socially included. This study will be presented in the form of two chapters, the first one in order to understand the influence of emotional factors throughout the stages of cosmetics purchase decision process that mitigate the aesthetic effects of aging in women belonging to economic class C. The second chapter aims to know the dynamics of aesthetic care and the decision of buying cosmetic products subject to the financial situation of these elderly. Therefore, it appears as a descriptive exploratory study that seeks greater familiarity with the problem so as to make it explicit. It also qualitative, because it is based on samples and open questions without pre-determined response options, allowing to know the perceptions, evaluations, feelings and judgments of people interviewed. We used the focus group technique. Participated 32 women, aged 60 to 80, of different levels of schooling, residents of a northern municipality, Rio Grande do Sul. The research took place in the second half of 2014, after approval by the Ethics Committee of the Universidade de Passo Fundo. The conclusion of the study revealed the influence of emotional factors in the purchase of cosmetics decision, that emotional factors take precedence and intervene in the cosmetics purchase decision process and aesthetic issue has a very important role in women's lives and, with aging and the consequent appearance of signs of age, the cosmetics assumes the function of alleviating the loss of the youthful appearance and aesthetic negative impact of this phase. When researching the dynamics of beauty treatments, it was observed that, despite the limited budget, these elderly routinely get aesthetic products and services, preserve a routine care with their appearance, with the health and quality of life